A critical comparative analysis on the suitability of the traditional laws in governing cyber pornography in Malaysia and in England and Wales / Khairul Idzwan Kamarudzaman … [et al.] - Kamarudzaman, Khairul Idzwan; Hamsidi, Mohd Akmal; Badarudin, Am' Syaridha Nadiya; Ariffin, Nurul Nadia (Faculty of Law, 2009)
This research is a critical comparative analysis on the suitability of the traditional laws in governing cyber pornography in Malaysia where special reference to the laws in England and Wales has been made. This study sets out to discover the suitability of the Malaysian traditional laws such as the Penal Code, the Film Censorship Act 2002 and the Printing Presses and Publications Act 1984 to govern cyber pornography. This is due to the fact that Malaysia has its very own cyber law which is the Communications and Multimedia Act 1998 and yet, in England and Wales, they apply their traditional laws to govern the offence. We found that the traditional laws may be suitable to govern cyber pornography but the traditional laws need to be amended and updated to include cyber environment so as to ensure their suitability to govern cyber pornography in Malaysia.